2016
DOI: 10.3855/jidc.8014
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant enterococci in the hospital environment: detection of novel vancomycin-resistant E. faecium clone ST910

Abstract: Introduction: The role of the hospital environment as a reservoir of resistant bacteria in Tunisia has been poorly investigated; however, it could be responsible for the transmission of multidrug-resistant bacteria. The objective was to study the prevalence of Enterococcus in the environment of a Tunisian hospital and the antibiotic resistance phenotype/genotype in recovered isolates, with special reference to vancomycin resistance. Methodology: A total of 300 samples were taken (March-June, 2013) and inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 26 publications
(41 reference statements)
2
32
0
Order By: Relevance
“…isolated resistant E. faecium ST80 from humans in South Africa, and this clone was reported for the first time by Dziri et al . from environmental samples in a Tunisian hospital and by Elhani et al . also in Tunisia.…”
Section: Discussionmentioning
confidence: 89%
“…isolated resistant E. faecium ST80 from humans in South Africa, and this clone was reported for the first time by Dziri et al . from environmental samples in a Tunisian hospital and by Elhani et al . also in Tunisia.…”
Section: Discussionmentioning
confidence: 89%
“…Fischer et al (2013) also reported the association between Tn916 and tet(M) in tetracycline-resistant S. agalactiae in camel in Kenya 86 . Similarly, IS 16 was found in vancomycin-resistant E. faecium (ST80, ST180 and ST910) in humans and the environment in Tunisia 69,70 . Investigations into the association between MGEs and resistance genes were limited by few studies (n=22 studies) on MGEs.…”
Section: Resultsmentioning
confidence: 79%
“…Similarly, Lochan et al (2016) 30 in South Africa, Dziri et al (2016) 20 and Elhani et al (2014) 69 in Tunisia isolated resistant E. faecium ST80 from humans. For the first time, E. faecium ST80 was isolated from environmental samples in a hospital in Tunisia by Elhani et al (2013) 69 and Dziri et al (2016) 70 . Transmission of this resistant clone to animals is possible, although not yet reported.…”
Section: Resultsmentioning
confidence: 89%
“…Molecular typing studies of E . faecalis can help to obtain better knowledge of the genetic relatedness within this bacterium and have identified the relative evolutionary of lateral gene transfer among these strains (Dziri et al, ; Zischka et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As sequence-based, MLST typing provides stable bacterial isolates, molecular diversity is consistent in laboratories all over the world. Molecular typing studies of E. faecalis can help to obtain better knowledge of the genetic relatedness within this bacterium and have identified the relative evolutionary of lateral gene transfer among these strains (Dziri et al, 2016;Zischka et al, 2015).…”
mentioning
confidence: 99%